LKB1 deficiency-induced metabolic reprogramming in tumorigenesis and non-neoplastic diseases - Yanghe Zhang; Qingfei Meng; Qianhui Sun; Zhi-Xiang Xu; Honglan Zhou; Yishu Wang (Elsevier, 2021)
Background: Live kinase B1 (LKB1) is a tumor suppressor that is mutated in Peutz-Jeghers syndrome (PJS) and a variety of cancers. Lkb1 encodes serine-threonine kinase (STK) 11 that activates AMP-activated protein kinase (AMPK) and its 13 superfamily members, regulating multiple biological processes, such as cell polarity, cell cycle arrest, embryo development, apoptosis, and bioenergetics metabolism. Increasing evidence has highlighted that deficiency of LKB1 in cancer cells induces extensive metabolic alterations that promote tumorigenesis and development. LKB1 also participates in the maintenance of phenotypes and functions of normal cells through metabolic regulation. Scope of review: Given the important role of LKB1 in metabolic regulation, we provide an overview of the association of metabolic alterations in glycolysis, aerobic oxidation, the pentose phosphate pathway (PPP), gluconeogenesis, glutamine, lipid, and serine induced by aberrant LKB1 signals in tumor progression, non-neoplastic diseases, and functions of immune cells. Major conclusions: In this review, we summarize layers of evidence demonstrating that disordered metabolisms in glucose, glutamine, lipid, and serine caused by LKB1 deficiency promote carcinogenesis and non-neoplastic diseases. The metabolic reprogramming resulting from the loss of LKB1 confers cancer cells with growth or survival advantages. Nevertheless, it also causes a metabolic frangibility for LKB1-deficient cancer cells. The metabolic regulation of LKB1 also plays a vital role in maintaining cellular phenotype in the progression of non-neoplastic diseases. In addition, lipid metabolic regulation of LKB1 plays an important role in controlling the function, activity, proliferation, and differentiation of several types of immune cells. We conclude that in-depth knowledge of metabolic pathways regulated by LKB1 is conducive to identifying therapeutic targets and developing drug combinations to treat cancers and metabolic diseases and achieve immunoregulation.